Palm Oil Plantation in Indonesia: A Question of Sustainability - Wahyu Indriyadi (Salus Cultura: Jurnal Pembangunan Manusia dan Kebudayaan, 2022)
The soaring price of cooking oil and the shortage of supply in Indonesia since December 2021 have brought the Indonesian palm oil industry back into the spotlight. Indonesia is one of the largest palm oil producers in the world. Although oil palm plantations are recognized as having a major role in alleviating poverty in Indonesia, there is a lot of controversy surrounding the Indonesian palm oil industry, both in terms of poverty alleviation itself and in terms of environmental damage it caused. Using exploratory qualitative method, this paper argues that the palm oil industry controversy stem from different eco-centric and technocentric views of producer and importer countries on how to achieve sustainable agriculture. Using Indonesia as a case, the results shows that arguing palm oil’s role in alleviating poverty and efforts in reducing environmental impact in Indonesia is not enough to quell palm oil industry controversies. The existing sustainability certification system such as RSPO and ISPO are seen as a technocentric solution that is ineffective and inadequate, whereas eco-centric unclear concept of sustainability and the complexity of the palm oil industry production chain is seen as contradictive. The results shows Indonesia needs to further strengthen its perspective on sustainability with more openness of data and improvement of systems in order to overcome the polarization of the narrative that has grown distrust of the palm oil industry. Negative sentiment toward the palm oil industry will not only harm Indonesia's socio-economic status but can also harm the environment, because importing countries may have to abandon palm oil even though they yet have an alternative that is more sustainable than palm oil.